Viabilização da Confecção de Moldes de Areia com Reaproveitamento da black dross de Alumínio - Silva, Raphael Oliveira da (Universidade Federal de São Carlos, 2026)
For Known for over 200 years, aluminum has dominated the industrial, metalworking, food, and aerospace markets, thanks to its remarkable structural capacity and versatility. In the automotive sector, for example, it is highly demanded for its low density and high mechanical strength, which allows for the construction of lighter chassis for electric vehicles, offsetting the weight of the batteries. However, the processes for obtaining metallic aluminum generate a significant amount of waste. While the production of primary aluminum results in a slag called white dross, the production of secondary aluminum is responsible for generating black dross. This work aimed to enable the reuse of black dross (BD) in the manufacture of molds for metal casting. Samples of BD were collected at Alux do Brasil, in partnership with Companhia Brasileira de Alumínio (CBA). These were characterized by scanning electron microscopy with energy-dispersive spectroscopy (SEM/EDS) and X-ray diffractometry (XRD). They underwent hydrometallurgical leaching processes in distilled water (ABD) or anhydrous glycerol (GBD) to dissolve NaCl and KCl salts. Percentages of ABD were incorporated into silica sand in samples named T10, T20, T25, T40, T50, and T50* in the presence of alkaline resin and pyridine catalyst. Uniaxial tensile tests were performed on the ABD samples. For field testing, a product was modeled using the 3D design software "Inventor". Next, a prototype made of acrylonitrile butadiene styrene (ABS) polymer was printed using CURA software and a 3D printer. A sand mold was made with the best condition sample, T25, into which an aluminum alloy was melted and poured. The product obtained by the silica sand mold casting process with incorporated black dross proved promising; the mold remained stable and showed good thermal and mechanical resistance to metallostatic pressure, allowing the possibility of applying this method in manufacturing processes for casting aluminum alloys.
Enabling the Production of Sand Molds Using Recycled Black Aluminum Slag
Keywords: black dross; lixiviação; molde de fundição; black dross; leaching; mold; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 9. Indústria, Inovação e Infraestrutura